Redistribusi Pendapatan : Peran BAZNAS pada Ketimpangan dan Kemiskinan di Indonesia - Khasanah, Miftakhul Fauziyah; Eka Ristanti, Frida; Nur Asiyah, Binti; Mashudi, Mashudi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
This study analyzes the role of zakat in promoting social justice and income redistribution in Indonesia, using BAZNAS National financial reports from 2022–2023 as a case study. Employing a descriptive quantitative approach, the research evaluates collection efficiency, distribution effectiveness, asnaf allocation, and the estimated impact on poverty and inequality. The findings show an 18.9% increase in zakat collection, though still low relative to national potential (CER 0.28%). Distribution effectiveness reached 78.24%, with the largest allocations assigned to the fakir and fisabilillah categories. The average transfer per beneficiary amounted to Rp619,380 (1.18× the national poverty line), indicating the effectiveness of zakat as a micro-level redistributive tool. However, its macro-level impact on reducing inequality remains limited. The results highlight the need for greater collection scale.